Theoretical-Philosophical insight about in vitro fertilization based on the Hans Jonas thought - Mônica OB Oriá; Leila MP Moraes; Lorena B Ximenes; Rui VO Moreira (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
The couple infertility is a dysfunction at the level of human reproduction, which has evolved since remote times. Some approaches have emerged from evolutions in technology not to cure infertility, but to reach successfully the desired offspring. In this article, we have approached in vitro fertilization (IVF) specifically; according to the strategy applied by many infertile couples in a variety of locations in Brazil. The aim of this study was to conduct a theoretical-philosophical discussion about IVF based on Hans Jonas responsibility principle. Hans Jonas is known as the philosopher who defends nature and humanity. Jonas states that the concept of responsibility implies on the must-being and must-doing, the latter as someone's reply to the must-being. Hence, it is critical to assure the intrinsic right of the subject. Thus, this intrinsic right of the embryo regards the right to live, never to die, a death induced simply by a human action. In Jonas theory, the best is not necessarily what is to come, but something to be conserved in opposite to a worse upcoming scenario. Therefore, re-thinking is needed, instead of advances on genetic manipulation, being conservative and provident in our attitudes remains critical.